Characteristics of soursop natural puree and determination of optimum conditions for pasteurization - A., Umme; Asbi, B.A.; Y., Salmah; A.H., Junainah; B., Jamilah (Elsevier, 1997)
The physico-chemical and microbiological characteristics of soursop natural puree were determined. The analysed parameters were: pH, titratable acidity, soluble solids, ascorbic acid, reducing sugars, viscosity, pectinesterase activity and cloud stability. A response surface methodology was used to establish the optimum conditions for pasteurization of soursop (Annona muricata L.) natural puree (2:1 w/v). In this study time-temperature combinations in the range of 15-120 sec and 50-90°C were the independent variables and their effects on enzyme inactivation and vitamin C retention were evaluated. The results implied an optimum pasteurization condition to be 69 sec and 78.8°C at pH 3.7.